Paget-Schroetter Syndrome: An Unusual Case of Upper Extremity Deep Vein Thrombosis - Pereira Fontes, Carla; M. Teixeira, Andreia; Manuel, Micaela; Fonseca, Samuel (Portuguese Journal Internal Medicine, 2022)
Paget-Schroetter syndrome (PSS), also known as effort thrombosis, refers to a rare form of primary thrombosis of the subclavian vein at the costoclavicular junction, which occurs after repeated strenuous upper limb activity. Usually, it involves an anatomical factor contributing to its aetiology, with young athletes being the most affected patients. We report an uncommon presentation of PSS complicated by pulmonary embolism in a 50-year-old man following mode[1]rate activity of upper extremities and in the absence of anatomical obstruction or other thrombotic risk factors. After conventional anticoagulant treatment, a favourable outcome was achieved. Due to the high risk of morbidity and mortality, early diagnosis and treatment essential for good outcomes.